Dynamic Mechanical Analysis of PLA Produced by FFF Additive Manufacturing Technology after DCSBD Plasma Treatment - Kohutiar, Marcel; Janík, Róbert; Krbata, Michal; Fekiač, Jozef Jaroslav; Kakošová, Lucia; Mikuš, Pavol (Manufacturing Technology Journal, 2025)
Dynamic mechanical analysis (DMA) is an important method for evaluating the viscoelastic properties of polymeric materials, especially when investigating their mechanical response to various manufacturing parameters and surface treatments. In recent years, DMA analysis has been intensively used, among others, for the analysis of polylactide (PLA) produced by the fused filament fabrication (FFF) additive technology. The present study focuses on the effect of DCSBD plasma treatment on the dynamic-mechanical properties of PLA samples with different infill geometries (Line, Rectilinear and Concentric). In the study, experimental PLA samples were subjected to DMA analysis in the temperature range of 40 °C to 90 °C in order to analyze the changes in their viscoelastic properties after plasma discharge surface treatment. The results showed a decrease in the glass transition temperature (Tg) for all tested samples, while the extent of the decrease depended on the infill geometry used. The most significant changes were observed in samples with Rectilinear infill, which showed the best mechanical stability after plasma treatment. The study shows that plasma treatment can influence the mechanical properties of PLA products, opening new possibilities for optimizing their processing, reuse and application in technical areas requiring controlled mechanical response.
Keywords: Polylactic acid (PLA); Dynamic mechanical analysis (DMA); DCSBD surface treatment; Additive manufacturing; Fused filament fabrication (FFF); Glass transition temperature (Tg)